Liquidity, Leverage, Profitability, Coupon Rate, and Maturity Structure: Determinants of Corporate Bond Ratings - Sitorus, Elly Helena; Dewi, Vera Intanie (E-Jurnal Akuntansi; Vol 35 No 6 (2025)DO - 10.24843/EJA.2025.v35.i06.p14, 2025)
Recent instances of default among companies in the Basic Materials sector—despite their investment-grade bond ratings—have raised concerns about the reliability of these ratings as indicators of creditworthiness. Investment-grade classifications are intended to signal a firm’s relatively robust capacity to meet its debt obligations and are typically grounded in assessments of key financial metrics. This study investigates the extent to which liquidity, leverage, profitability, coupon rate, and bond maturity influence bond ratings. A purposive sampling approach was adopted, yielding a sample of ten firms observed over the period 2020 to 2024. Employing panel data regression, the analysis explores both the individual and joint effects of the selected variables on bond ratings. The findings suggest that each of the examined factors—liquidity, leverage, profitability, coupon rate, and maturity—exerts a significant influence on bond ratings, both independently and in combination. Keywords: Liquidity; Leverage; Profitability; Coupon; Bond Maturity; Bond Rating